Analysis of the corrosion rate of SS 316l metal in a tsunami detection tool in seawater media - Gusti Ayu Arwati I; Alfattah Muhammad; Maryani Yeyen; Suprihatiningsih Wiwit; Yuliarty Popy (BIO Web of Conferences)
Indonesia frequently faces tsunami disasters, making the need for early detection tools essential. As a technological innovation, the inabuoy was created. This device uses underwater sensors to provide early warnings for tsunamis. Inabuoy is installed in areas prone to tsunamis and uses a 316L stainless steel frame submerged in seawater. Due to its underwater position, it is subject to corrosion from seawater with a pH of 7 to 8.5. This study aims to determine the corrosion rate of stainless steel 316L, a wmical method with seawater media with variations of 0, 24, 48, 72, and 96 hours of immersion. Analysis of the corrosion rate of 316L stainless steel specimens in seawater media with immersion of 0, 24, 48, 72, and 96 hours by potentiodynamic electrochemical method. It was found that the lowest corrosion rate data occurred on specimens of 0 hours of immersion with an average value of 4.5681 x 10-3 mmpy while the highest corrosion rate occurred in specimens that were immersed for 96 hours, showing an average value of 8.6811x10-3 mmpy, this shows the value of the corrosion rate that occurs increases with the length of immersion time. This research contributes to achieving SDGs 9, 11, 13, and 14.